Improvement of ethanol productivity and energy efficiency by degradation of inhibitors using recombinant Zymomonas mobilis (pHW20a‐fdh). Issue 9 (5th July 2013) - Dong, Hong‐Wei; Fan, Li‐Qiang; Luo, Zichen; Zhong, Jian‐Jiang; Ryu, Dewey D. Y.; Bao, Jie
Abstract Toxic compounds, such as formic acid, furfural, and hydroxymethylfurfural (HMF) generated during pretreatment of corn stover (CS) at high temperature and low pH, inhibit growth of Zymomonas mobilis and lower the conversion efficiency of CS to biofuel and other products. The inhibition of toxic compounds is considered as one of the major technical barriers in the lignocellulose bioconversion. In order to detoxify and/or degrade these toxic compounds by the model ethanologenic strain Z. mobilis itself in situ the fermentation medium, we constructed a recombinant Z. mobilis ZM4 (pHW20a‐fdh) strain that is capable of degrading toxic inhibitor, formate. This is accomplished by cloning heterologous formate dehydrogenase gene (fdh) from Saccharomyces cerevisiae and by coupling this reaction of NADH regeneration reaction system with furfural and HMF degradation in the recombinant Z. mobilis strain. The NADH regeneration reaction also improved both the energy efficiency and cell physiological activity of the recombinant organism, which were definitely confirmed by the improved cell growth, ethanol yield, and ethanol productivity during fermentation with CS hydrolysate. Biotechnol. Bioeng. 2013; 110:2395–2404. © 2013 Wiley Periodicals, Inc.